Представники родини Cupressaceae F.W. Neger у ландшафтах дендропарку “Тростянець” - Iljenko, О.О.; Medvedev, V.A.; Rahinskaja, M.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The brief historical background on the introduction of species of Cupressaceae F.W. Neger family in Dendropark Trostjanets are shown. The dynamics of species composition and reproductive capacity of individual members of this family in terms of the dendropark are investigated.